Green Tea Catechin, EGCG, Suppresses PCB 102-Induced Proliferation in Estrogen-Sensitive Breast Cancer Cells - Kimberly Mantzke Baker; Angela C. Bauer (International Journal of Breast Cancer)
The persistence of polychlorinated biphenyls (PCBs) in the environment is of considerable concern since they accumulate in human breast tissue and may stimulate the growth of estrogen-sensitive tumors. Studies have shown that EGCG from green tea can modify estrogenic activity and thus may act as a cancer chemopreventive agent. In the present study, we evaluated the individual and combined effects of PCB 102 and EGCG on cell proliferation using an estrogen-sensitive breast cancer cell line MCF-7/BOS. PCB 102 (1–10 μM) increased cell proliferation in a dose-dependent manner. Furthermore, the proliferative effects of PCB 102 were mediated by ERα and could be abrogated by the selective ERα antagonist MPP. EGCG (10–50 μM) caused a dose-dependent inhibition of PCB 102-induced cell proliferation, with nearly complete inhibition at 25 μM EGCG. The antiproliferative action of EGCG was mediated by ERβ and could be blocked by the ERβ-specific inhibitor PHTPP. In conclusion, EGCG suppressed the proliferation-stimulating activity of the environmental estrogen PCB 102 which may be helpful in the chemoprevention of breast cancer.